Single‐layer dual‐broadband circularly polarised annular‐slot antenna for WLAN applications. Issue 1 (11th December 2017) - Ge, Lei; Sim, Chow‐Yen‐Desmond; Su, Hsin‐Lung; Lu, Jun‐Yu; Ku, Chin
Abstract : This study proposes a single‐layer dual‐broadband circularly polarised (CP) antenna that operates at 2.4, 5.2 and 5.8 GHz for wireless local area networks (WLAN) applications. An annular‐slot antenna loaded with a lightning‐shaped slot for achieving good CP radiation in the WLAN 2.4 GHz band is initially studied. To cover the WLAN 5.2 GHz band as well, the inner circular patch of the aforementioned design is modified as an inner ring patch loaded with a notch and a narrow U‐shaped strip. By further embedding a crescent parasitic element into the circular slot of the inner ring patch, the upper CP band is significantly broadened to cover the WLAN 5.8 GHz. Accordingly, the final design can exhibit two wide 3 dB axial ratio bands of 13.3% (2.24–2.56 GHz) and 16.9% (5.01–5.94 GHz), and their corresponding 10 dB impedance bandwidths are 25.9% (2.21–2.86 GHz) and 25.9% (5.05–6.54 GHz). With the advantages of compact size, low‐cost, easy integration and dual‐broad CP bands, the proposed designs are very attractive for modern wireless communication systems, especially for WLAN applications.